Pest-arthropods notified by the zoonosis control sector from Divinópolis – MG - Fonseca, A. R.; Pereira, M. H.; Rocha, B. F.; Sousa, F. F. (Scientific Electronic Archives, 2017)
Arthropods stand for the largest phylum among animals and are plentiful in practically all the terrestrial ecosystems. This study intended to conduct the survey of the occurrence of this taxon in the municipality of Divinópolis – MG based upon the occurrence file attended to by the Environmental Surveillance Sector of the municipality in the years of 2011 to 2013, from the information contained in the form for the notification. In the period studied; 3, 960 occurrences were recorded, 1,208, 1,254, and 1,498 being in the years of 2011, 2012, 2013 respectively. A higher number of records were obtained for mosquitoes (n = 2041), ticks (n = 721), scorpions (n = 437) and fleas (n = 436). Such information is important to the planning and accomplishment of action relative to the activity of promotion of health, prevention and control of synanthropic organisms and consequently of the transmitted diseases